Attacking stressed klebsiella pneumonia biofilm with Wi-Fi - Tay, Mavis Si Min (2017)
In this current world of technology, it is easy to realise how much we rely on Wi-Fi for data connection. The increase in reliance spurs many studies on the possible interaction between Wi-Fi and the human body. In this study, possible antibacterial effect of Wi-Fi on stressed cells. To investigate the antibacterial effect, K. pneumoniae (KP-1) cells were considered, with varying health of cells by varying the Magnesium and Calcium in the media. Through this study, it is speculated that the motility of the cells do affect how the bacterial pathogens react to susceptible external stresses. This paper takes close references to papers written by the team whom worked on similar stresses on different bacteria. It is motivating to observe that the amount of Magnesium and Calcium influences the bacteria under both control and 2.4GHz of Wi-Fi exposure. The results from the optical density of both Wi-F and controlled, and, for planktonic cells and biofilms, varies in the same way respectively for the same amount of Magnesium. This study also shows that KP-1 is influenced by the exposure of Wi-Fi. With reference to the thesis written by Najmah and Nicholas, this could possibly mean that non-motile bacteria are more susceptible to the exposure of Wi-Fi.